How do swimmers pace the 400 m freestyle and what affects the pacing pattern?. Issue 6 (2nd November 2021) - Barroso, Renato; Crivoi, Everton; Foster, Carl; Barbosa, Augusto Carvalho
ABSTRACT: To describe the pacing pattern of elite 400 m freestyle swimmers, understand how athletes select the first half compared to their 200-m race pace, and correlate critical speed (CS) and D' with pacing parameters. The best all-time 400 m performances were obtained, and 200 m performances were retrieved from the same competition. Twenty-four performances were selected and, when possible, 50 m-splits were obtained. CS and D' were calculated based on the 200 m and 400 m performances. Most athletes adopted a parabolic pacing pattern. Performance in the 400 m correlated with that of the 200 m (rho = 0.418, p = 0.042), the % difference between 200 m performance and 200 m split correlated with CS (rho = −0.595, p = 0.002) and with D' (rho = 0.808, p < 0.001). The correlation between D' and % difference between average speed and CS was nearly perfect (rho = 1.000, p < 0.001). Recommendations of having the first half of the 400 m 4–5 s slower than their 200 m race do not seem to be appropriate for all swimmers and depends on physiological abilities.